1998
DOI: 10.1107/s0909049597020244
|View full text |Cite
|
Sign up to set email alerts
|

Application of synchrotron radiation in investigation of metal-ion release from a hip replacement prosthesis

Abstract: The aim of the present study was to measure very low concentrations of Al, V, Fe, Cr and other metal elements in a matrix of P, S, Cl, Ca and other constituent elements of the human body. These metal elements were released from a failed total hip replacement prosthesis into the surrounding tissues. The experimental results have been compared with those from proton-induced X-ray emission spectroscopy of the same specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…It is a challenge to detect, quantify, and perform elemental analysis of small seized, scattered particles 3,28,29 . Several in vitro studies have indicated that small corrosion metal particles in direct cell contact and in a high concentration may cause cell damage 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenge to detect, quantify, and perform elemental analysis of small seized, scattered particles 3,28,29 . Several in vitro studies have indicated that small corrosion metal particles in direct cell contact and in a high concentration may cause cell damage 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…This method is applied to assess various kinds of biomedical object, i.e., the intoxication of Hg [2,3], distribution of cis-Pt in cancer therapy [4,5],distribution of Cu, Se, and Zn of renal cancer [6], metal-ion release from a hip replacement prosthesis [7], and metal deposition of Parkinson disease. It can evaluate very low contents in the order of picograms per gram of specific elements.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions and responses of cells to foreign metal elements have been widely investigated in the past decades. The interactions between cells and metal ions or particles, has been investigated (invivo and in-vitro), in the case of wear debris and corrosion in metal implants (Wang, J. C. et al (1999); Ektessabi, A. et al (1998); Ektessabi, A. et al (1997); Wang, J. Y. et al (1996); Ektessabi, A. and Wennerberg, A. (1995); Shanbhag, A. S. et al (1994)).…”
Section: Introductionmentioning
confidence: 99%
“…In several previous studies, Ektessabi et al (Ektessabi, A. et al (1998); Ektessabi, A. et al (1997); Ektessabi, A. and Wennerberg, A. (1995)) applied PIXE, micro-beam PIXE, and SR-XRF to the investigation of human tissues around total hip replacements where SUS316L and Ti-6Al-4V had been inserted into the human body for long periods of time.…”
Section: Introductionmentioning
confidence: 99%